KARAKTERISITIK DAN KEUNGGULAN ANGGUR VARIETAS â€œRed Pinceâ€ (Prabu Bestari) dan â€œCardinalâ€ (Probolinggo Super) di Kota Probolinggo - Prahardini, Amik Krismawati, (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2011)
In accordance wiyh the development program of horticultural by agricultural service of EastÂ Java Provinced, then the grape culture in Probolinggo, expecially urban specific need to be growth.Â The development of grape plants in Probolinggo is one of local government efforts toÂ get back the Probolinggo image as city ofÂ â€œBAYUANGGAâ€Â (Bayu means wind, Angga means grape and mango).Â The widthÂ ofÂ grape yields in Probolinggo in the year of 2002 is around 1.442 ha by total amounts 110 tons, yet the level of productivity is still lower, approximately 77.36Â kuintals per ha. The potential of grape plants in Probolinggo need to be improved considering that the condition of agoecology sufficiently supporting to culture grape successfully.Â The main and dominant area of development (Subdistrict of Kademangan, Wonoasih, and Mayangan)Â ia aluvial soil, located in 10 â€“ 37 m asl, by plant topography ( 3%), the intensity of rainfall annually ia around 4 â€“ 5 wet month and 7 month dry. The temperature is about 30 â€“ 32oC and the soil acidity ia about 5.5 â€“ 6.5.Â The research method was to make inventory and exploration grape plants with respect to the information on the condition.Â Inventory and exploration wereÂ conductedÂ atÂ Probolinggo City from MeiÂ untilÂ September 2007. The aim of this study were to find out the varieties which are widely developed are variety of Red Prince (Prabu Bestari) and Cardinal (Probolinggo Super). The two varieties are amountedÂ approximatelyÂ 60 â€“ 70% ogf total grape seedlings in Probolinggo, whereas 30 â€“ 40% other varieties are Belgie, Alphonso Lavelle (Probolinggo Biru-81).Â Furthermore, the variety of Red Prince is favorable among farmers for its relative high price.Â The price in farmers level, grape variety of Red Prince is around Rp 10.000 to 12.500 per kg, whereas in the retailer level is around Rp 15.000 to 17.500 per kg.Â The grape of Red Prince and Cardinal are superior and excited by many people for its morphological, charming red and sweet.Key wordÂ : Vitis sp, potential, advantageous, varieties, RedPrince, Cardinal, Probolinggo CityÂ Â Â Â